Reform of Ataturk: development of the Turkish language - Balahozhaeva, A.; Kortabaeva, G. (Journal of Oriental Studies, 2016)
This article covers the period of Turkish language, including the reform of Atatürk. Ataturk, seeking to bring Turkey to the levelof modern civilization, has implemented a number of reforms in the country. All languages other than Turkish, were banned. Thewhole system of education based on the upbringing of the Turkish spirit of national unity. These postulates have been proclaimed in theConstitution in 1924.